HAKIKAT DAN KARAKTERISTIK MANUSIA (INSAN, BASYAR, AN NAS DAN UMMAH) DAN RELASINYA DENGAN PROSES KEPENDIDIKAN - Hendri Irawan (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2022)
Â Â The aim of this research is to find out the nature and characteristics of human beings (insan, basyar, an-nas and ummah) and their relation to the educational process so that they can be used as reading sources or references. This research is a qualitative research with a library research approach (literature study), namely research whose subject is in the form of library literature. Sources of data from documentation that comes from books and scientific journals related to the object of research. The data collection technique in this study was a documentation technique, namely data collection by selecting data that correlated with the research title. The documentation method in this study is by collecting data, analyzing data according to the theory to draw conclusions. The results showed: The nature and characteristics of humans (humans, basyar, an nas and ummah) are created beings. In this human creation, humans have been given by His creator (God) the potentials to live which in this case relate to the concept of human nature. In the Qur'an Allah mentions the word human with various names according to their characteristics such as insan, basyar, al-nas and ummah. Then in the nature and characteristics of humans and their relationship to the educational process is divided into three parts, the first is human potential according to the Qur'an, the second is the implications of basic human potential in the process of Islamic education, and the third is the nature of human nature and its relationship with the educational process. Keywords: Human nature, human characteristics, relationships, education.